2015
DOI: 10.1007/s00018-015-1851-0
|View full text |Cite
|
Sign up to set email alerts
|

La FAM fatale: USP9X in development and disease

Abstract: Deubiquitylating enzymes (DUBs), act downstream of ubiquitylation. As such, these post-post-translational modifiers function as the final arbitrators of a protein substrate’s ubiquitylation status, thus regulating its fate. In most instances, DUBs moderate the absolute level of a substrate, its locality or activity, rather than being an “all-or-none” phenomenon. Yet, disruption of this quantitative regulation can produce dramatic qualitative differences. The ubiquitin-specific protease 9X (USP9X/FAM) is a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
188
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(194 citation statements)
references
References 121 publications
(157 reference statements)
4
188
2
Order By: Relevance
“…10 How could the loss of Usp9x culminate in oligodendrogenesis? At this stage this is unclear, however previous reports of interactions between USP9X and members of the Notch signaling pathway, 29 coupled with the reduced expression of Notch pathway members revealed here (Hes5, Fabp7 and Tnc) suggests that a primary role for USP9X, in the context of NSCs, is the maintenance of their identity and self-renewal capacity. Identification of why the loss of Usp9x potentially biases NSCs toward oligodendrocytic differentiation will require a more comprehensive analysis of the USP9X interactome, coupled with proteomic analysis of NSCs lacking this enzyme.…”
contrasting
confidence: 52%
“…10 How could the loss of Usp9x culminate in oligodendrogenesis? At this stage this is unclear, however previous reports of interactions between USP9X and members of the Notch signaling pathway, 29 coupled with the reduced expression of Notch pathway members revealed here (Hes5, Fabp7 and Tnc) suggests that a primary role for USP9X, in the context of NSCs, is the maintenance of their identity and self-renewal capacity. Identification of why the loss of Usp9x potentially biases NSCs toward oligodendrocytic differentiation will require a more comprehensive analysis of the USP9X interactome, coupled with proteomic analysis of NSCs lacking this enzyme.…”
contrasting
confidence: 52%
“…We showed that the physical association of USP9X with centrosomes is cell cycle-dependent and mostly detected in S and G 2 phases. Remarkably, disrupting protein trafficking or the Golgi in polarized epithelia results in relocation or accumulation of USP9X, suggesting that this protein shuttles between a number of organelles and vesicles52. These observations highlight the need to interrogate USP9X–substrate interactions with approaches sorting specific subcellular compartments instead of more disruptive biochemical methods that extensively destroy cellular architectures52.…”
Section: Discussionmentioning
confidence: 99%
“…USP9X is involved in the regulation of cell adhesion molecules such as E-cadherin, chromosome segregation, NOTCH, and TGFb signaling as well as apoptosis (comprehensively reviewed in ref. 30).…”
Section: Introductionmentioning
confidence: 99%
“…In different cancers, USP9X can act as an oncogene or as a tumor suppressor gene in a context-dependent manner: USP9X is overexpressed in multiple carcinomas including lymphomas, nonsmall cell lung and breast cancer (30). The best described oncogenic function of USP9X derives from its role in promoting the deubiquitinylation and stabilization of antiapoptotic protein MCL1.…”
Section: Introductionmentioning
confidence: 99%